Virtual Platforms Skills Required by College of Education Lecturers for Instructional Delivery in Kogi State, Nigeria - Olorunleke, Adesanya Emmanuel; Olumuyiwa, Ayeni Bayonle; Bature, Shuaib Suleiman (Universitas Pendidikan Indonesia (UPI), 2024)
The shift in the mode of instructional delivery has necessitated the need for teachers at every level to acquire the skills and competencies needed to use virtual learning platforms and classrooms for their teaching activities. This is more important as colleges of education lecturers are responsible for producing the next generation of teachers. This study appraised the skills required by college of education lecturers in Kogi State, Nigeria for instructional delivery with virtual learning platforms and classrooms. The study was survey research. Four research questions and one hypothesis guided the study. The instrument for the study was a questionnaire. Lectures in colleges of education in Kogi State, Nigeria constituted the population for the study. The sample of the study was 100 Science Education lecturers, sampled from two colleges of education. Data was analysed using percentages, mean, standard deviation, t-tests, and ANOVA statistics. The study found that lecturers required skills in planning, engaging in social interactions, presentation, technical, and assessment for virtual; learning classrooms. Also, no significant difference in virtual learning platform skills needed by college of education lecturers based on school type, gender, and qualifications. However, lectures differed significantly based on years of teaching experience. The study has improvements in awakening Lecturers to apprise their virtual platforms usage skills thereby prompting them to seek for improvement translating to production of teachers with twenty-first century teaching skills.